Fashioning a national art: Baroda's royal collection and art institutions (1875-1924) - Priya Maholay-Jaradi (New Delhi: Oxford University Press, 2016)
This book is about how the Baroda Palace Collection came into being under its patron-collector Maharaja Sayajirao Gaekwad III. It throws light on Sayajirao's private collecting practice that shaped Baroda's modern art and craft institutions and industries. Taking rare archival records from 1875 as its point of departure, the work demonstrates how the Maharaja's private collecting practice and its egalitarian ideas both shaped and participated in the institutional, industrial, and commercial realms within Baroda, India, and Euro-America. For the first time, a native prince emerged simultaneously as an exemplar of international collecting, an arbiter of taste and value, and a spokesperson and strategist for a colonized India's national concerns. The book sheds light on numerous elite and subaltern plots: the role of Dewan T.0Madhavarao and other state officials as resource persons and advisors; a significant oil portraitist Tiroovengada Naidu, who preceded Raja Ravi Varma at Baroda; numerous contracts between European and native painters and sculptors; ivory craftsman, Neelakandan Asari; establishment of Baroda's premier polytechnic, Kalabhavan and the Nazarpaga and State Furniture Works; 'star pieces' on the exhibitions' trail such as the Baroda Screen and Baroda Balcony, select luxury goods inspired by Baroda designs and exhaustive loans' inventories for exhibitions.
Keywords: Art Museum Baroda; Art Collection India; Arts India; Arts